Livability Level As A Guideline Of Arrangement Of Suprapto Road City Walk Corridor In Bengkulu City - Rahzon Afryan; M. Sani Roychansyah (Departement of Architecture, Universitas Islam Indonesia, 2019)
Livable road corridors are corridors designed to accommodate the needs of all road users (motorists, cyclists and pedestrians). Livable Street provides a balance of activity between vehicles using the road corridor and the different communities there. At this time, Suprapto Road is a road corridor with a function as a commercial area. The government’s program to develop Suprapto Road in the future is by transforming it into a City Walk of Bengkulu City, this idea was stated by the Head of the Public Works and Housing Office of PUPR in Bengkulu, Mr. Rozy Ismawardi. The City Walk concept is not new, several places around the world have presented the City Walk concept in the corner of the city space, such as Clark Quay, Far East Square, and Orchard Road in Singapore. Through the City Walk concept, the local government can turn a dead old city into an active area. Related with the Bengkulu City government program above, a study is needed to get an idea of the level of livability if the city road in Bengkulu is used as a City Walk. Thus, it will objectify the factors that influence it while providing appropriate structuring guidelines for the City Walk that is Livable in Suprapto Street corridor. This study uses qualitative rationalistic methods through the perception of individuals in an effort to see, understand, and realize how the level of livability if a road functioned as a City Walk. This research begins with an observation activity on the condition of Suprapto Street in Bengkulu, complemented with the theory of livability and City Walk. Standard provisions and criteria are used to see what factors influence the level of livability in the road corridor. The research results will be the basis for determining the City Walk structuring arrangement for the Suprapto Street corridor. Keywords: livability, city walk, street’s space